'Filming the invisible': Barrie Gavin in conversation with John Wyver. Issue 1 (1st March 2021) - Wyver, John
Barrie Gavin (b. 1935) is a celebrated producer, director and writer who is best known for numerous programmes about music and musicians made primarily for BBC Television from 1964 onwards. He worked on numerous occasions with the conductors Pierre Boulez and Simon Rattle, and with them and other collaborators he has directed more than 90 films. In this conversation recorded in Leeds in June 2018 Gavin discusses with the writer and producer John Wyver his ideas about making music television, his innovative approaches to filmmaking, his profiles of composers including Luigi Nono, Karlheinz Stockhausen and Toru Takemitsu, and his working relationships with Boulez and Rattle.